Academic productivity of communication teachers at public universities. Contributions to the field of knowledge - Miranda-Gaibor, Christian Giovanny (2024)
Academic production in public university institutions in Ecuador reflects significant changes in publications at the national and international level. Thus, the research started from the quantitative approach, descriptive level, where the bibliometric indicator of the UNACH repository, publications were reviewed between 2014 to 2022. The main results showed that the teachers of the Communication Career generated a greater number of publications since 2019, especially in 2022. In addition, there is interest in academic production on regional research, magazines with preference in Spanish, without a tendency towards specific topics. It is concluded that, after strengthening public policies in research, anchored to the use of the Internet, they have generated a greater number of academic production, contributions that have given knowledge from a variety of topics of communication interest anchored to the social and cultural, however, still It is a path that requires overcoming challenges such as the non-native language to expand the number of readers in the field.